2013
DOI: 10.1074/jbc.m112.397604
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl 4-Hydroxlase Activity Is Essential for Development and Cuticle Formation in the Human Infective Parasitic Nematode Brugia malayi

Abstract: Background: Collagen prolyl 4-hydroxylases (C-P4H) are involved in the formation of extracellular matrices.Results: The full complement of C-P4H enzymes from the human infective parasite Brugia malayi have been bioinformatically, biochemically, and functionally characterized.Conclusion: C-P4H enzymes are essential for development in B. malayi.Significance: Unique features of these essential enzymes may be exploited in future control mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Additional research will be needed to characterize the particular molecular mechanisms at play, and the assay we describe can be interfaced with reverse genetic approaches to provide a genetic and mechanistic basis for the observed responses. To this end, we have developed a robust and reliable in vivo RNAi protocol to suppress genes of interest in the B. malayi L3 stage (Song et al ., 2010), whilst others have shown that RNAi can be applied to other life stages of the parasite in vitro (Aboobaker and Blaxter, 2003; Ford et al ., 2009; Landmann et al ., 2012; Singh et al ., 2012; Winter et al ., 2013; Luck et al ., 2016; Misra et al ., 2017; Verma et al ., 2017). This receptiveness to RNAi, combined now with assays to interrogate sensory phenotypes, advances B. malayi as a tractable system to better understand sensory biology in filarial worm parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research will be needed to characterize the particular molecular mechanisms at play, and the assay we describe can be interfaced with reverse genetic approaches to provide a genetic and mechanistic basis for the observed responses. To this end, we have developed a robust and reliable in vivo RNAi protocol to suppress genes of interest in the B. malayi L3 stage (Song et al ., 2010), whilst others have shown that RNAi can be applied to other life stages of the parasite in vitro (Aboobaker and Blaxter, 2003; Ford et al ., 2009; Landmann et al ., 2012; Singh et al ., 2012; Winter et al ., 2013; Luck et al ., 2016; Misra et al ., 2017; Verma et al ., 2017). This receptiveness to RNAi, combined now with assays to interrogate sensory phenotypes, advances B. malayi as a tractable system to better understand sensory biology in filarial worm parasites.…”
Section: Discussionmentioning
confidence: 99%
“…3′UTRs from Bm1_27305, Bm1_05425 and Bm1_25620 were amplified from B. pahangi genomic DNA (isolated as described previously [ 50 ]) using PfuUltra II Fusion HS DNA Polymerase (Agilent) (primers in Additional file 10 ). Products were cloned into pCR2.1-TOPO (Invitrogen) then subcloned into the Not I site downstream of firefly luciferase in pMir-Target (Origene) to generate plasmids pABR212 (Bm1_27305 3′UTR in pMir-Target), pABR210 (Bm1_05425 3′UTR in pMir-Target) and pABR211 (Bm1_25620 3′UTR in pMir-Target).…”
Section: Methodsmentioning
confidence: 99%
“…A ~1.7 kb Pst I/ Pst I fragment of this was cloned into pPD129.36 (Addgene) to create plasmid pADW0062 which was linearised with Not I and Hind III. In vitro transcription and preparation of endoribonuclease-prepared pools of complex siRNA (esiRNA) was carried out as described previously [ 50 ]. Larvae were harvested at either 4 or 5 days p.i.…”
Section: Methodsmentioning
confidence: 99%
“…elegans mutants with the orthologous gene from Brugia spp., even when the degree of conservation is significantly less than that of the respective Hsp90s [45]. While failure to rescue the mutant phenotype may reflect differences in the nature of the client proteins chaperoned by Hsp90 in Brugia and C.…”
Section: Hsp90 Differs In Free-living and Parasitic Nematodesmentioning
confidence: 99%